Penggunaan Aplikasi Canva Sebagai Media Penyuluhan Di Klinik Pratama Bertha - Frans Iko Rasaki; Fithry Tahel; Erwin Ginting (Gayaku Publisher, 2023)
The aim of carrying out community service activities is to fulfill the Tridarma obligations of higher education, secondly to provide useful training for doctors and nurses in the future for outreach in the community, for example in posyandu activities which are held every month or other counseling held at the Bertha Pratama Clinic. For the Bertha Pratama Clinic, counseling about health activities and about diseases, both in terms of the disease and how to deal with it, felt that it was obligatory to inform the public. Previously, at the Bertha Pratama Clinic, counseling was held every month, only in the form of manual discussions using only audio. In the current era of digitalization, counseling is not only delivered with audio but also accompanied by slides so that it is easier for the public to understand what the presenter is saying. Using Canva slides will be even more interesting to look at and very user friendly